Evolving concepts of hemodynamic monitoring for critically ill patients - Hamzaoui, Olfa (Indian J Crit Care Med, 2015)
The last decades have been characterized by a continuous evolution of hemodynamic monitoring techniques from intermittent toward continuous and real-time measurements and from an invasive towards a less invasive approach. The latter approach uses ultrasounds and pulse contour analysis techniques that have been developed over the last 15 years. During the same period, the concept of prediction of fluid responsiveness has also been developed and dynamic indices such as pulse pressure variation, stroke volume variation, and the real-time response of cardiac output to passive leg raising or to end-expiration occlusion, can be easily obtained and displayed with the minimally invasive techniques. In this article, we review the main hemodynamic monitoring devices currently available with their respective advantages and drawbacks. We also present the current viewpoint on how to choose a hemodynamic monitoring device in the most severely ill patients and especially in patients with circulatory shock.